Perbandingan Pengendalian Intern dan Pengendalian Manajemen Dalam Hubungannya Dengan Agency Theory - Hamfri Djajadikerta (Bina Ekonomi, 2004)
The agency theory deals with agency problems resulting from conflicts of interest that may emerge in contractual relationships. Agency relationship is a contract under which one or more persons (the principal(s)) engage another person to perform some service on their behalf which involves delegating some decision making authority to the agent. Differently informed or uncertain and different subjective interests give rise to conflicts of interest between contracting partners. If both parties to the relationships are utility maximizers, there is a good reason to believe that the agent will not always act in the best interests of the principal. Principals is concerned with how these agency problems can be minimized. In accounting domain, internal control systems and management control systems are two tools which principals have created to minimized the problem. The internal control systems is more concerned to rules and monitoring aspect to control the agent. The management control system is a process to influence agent with incentive contract thus it more concerned to human behavior aspect.